2019
DOI: 10.1128/jvi.00564-19
|View full text |Cite
|
Sign up to set email alerts
|

A Zoonotic Adenoviral Human Pathogen Emerged through Genomic Recombination among Human and Nonhuman Simian Hosts

Abstract: Genomics analysis of a historically intriguing and predicted emergent human adenovirus (HAdV) pathogen, which caused pneumonia and death, provides insight into a novel molecular evolution pathway involving “ping-pong” zoonosis and anthroponosis. The genome of this promiscuous pathogen is embedded with evidence of unprecedented multiple, multidirectional, stable, and reciprocal cross-species infections of hosts from three species (human, chimpanzee, and bonobo). This recombinant genome, typed as HAdV-B76, is id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 75 publications
1
44
0
Order By: Relevance
“…A third, archived genome from 1967, has been recently sequenced and reported to show near identity to the above two genomes as well (manuscript in preparation). As it was isolated from a human host and led to a respiratory illness and fatality, it has been renamed HAdV-76 (Dehghan et al, 2019), rather than "SAdV-35.3" or the original designation "21 + 16/16". These three genomes contain recombination events from SAdV-21 (chimpanzee), HAdV-21 (human), SAdV-27 (chimpanzee), and HAdV-16 (human) (Dehghan et al, 2013a;Dehghan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A third, archived genome from 1967, has been recently sequenced and reported to show near identity to the above two genomes as well (manuscript in preparation). As it was isolated from a human host and led to a respiratory illness and fatality, it has been renamed HAdV-76 (Dehghan et al, 2019), rather than "SAdV-35.3" or the original designation "21 + 16/16". These three genomes contain recombination events from SAdV-21 (chimpanzee), HAdV-21 (human), SAdV-27 (chimpanzee), and HAdV-16 (human) (Dehghan et al, 2013a;Dehghan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As it was isolated from a human host and led to a respiratory illness and fatality, it has been renamed HAdV-76 (Dehghan et al, 2019), rather than "SAdV-35.3" or the original designation "21 + 16/16". These three genomes contain recombination events from SAdV-21 (chimpanzee), HAdV-21 (human), SAdV-27 (chimpanzee), and HAdV-16 (human) (Dehghan et al, 2013a;Dehghan et al, 2019). This striking example underscores why AdVs may be one of the few, if not the only, model organisms to explore and understand the phenomenon of "amphizoonosis", that is, cross-species transmissions occurring in both directions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human adenoviruses (HAdVs) are non-enveloped, double-stranded DNA viruses and are divided into seven species (A–G). To date, approximately 100 types have been recognized according to genomic sequences ( https://hadvwg.gmu.edu/ ) (Seto et al 2011 ; Dehghan et al 2019 ). HAdVs are highly contagious pathogens that exhibit a variety of tissue tropisms, and cause many diseases, such as acute respiratory disease (ARD), gastroenteritis, cystitis, keratoconjunctivitis, carditis, meningoencephalitis, depending on the infection type.…”
Section: Introductionmentioning
confidence: 99%
“…Since both HAdV‐B21 and ‐B16 are human respiratory pathogens, it was suggested that SAdV‐B35 could be a nascent human respiratory pathogen. This idea proved prescient when a recent analysis of an adenovirus originally isolated from a fatal respiratory infection in a 6‐year‐old boy in 1965 revealed a virus genome nearly identical to SAdV‐B35 . This interspecies recombinant was typed as HAdV‐B76.…”
Section: Homologous Recombination In Human Adenovirus Evolutionmentioning
confidence: 99%